Review of current practices of Islamic microcredit and microfinancing in selected Muslim countries - Abdul Razak, Dzuljastri; Md Saad, Norma; Abdul Rahman, Abdul Rahim (Serials Publication, 2009)
Poverty is a major problem in most developing countries and majority of the governments of these countries have initiated some forms poverty alleviation programs to reduce poverty level in their respective countries. Studies have shown that microfinance is proven to be an effective tool to fight poverty in many developing countries, including Muslim countries. This study reviews the current practices of microcredit and microfinance in several Muslim countries namely Malaysia, Bangladesh, Indonesia and Sudan. The methodology used in this research is mainly literature survey. This study finds that Islamic microfinance industry is not yet well developed in Muslim countries. Indonesia, for example, has thousands of Islamic microfinance institutions operating in this country, however, many of those institutions have still not performed well and incurred losses in their operation. This study is only a preliminary research and the findings of this study will hopefully provide focal areas for further research in the near future.